Decentralization of Health and Education in Developing Countries : A Quality-Adjusted Review of the Empirical Literature - Channa, Anila; Faguet, Jean-Paul (Published by Oxford University Press on behalf of the World Bank, 2018)
We review empirical evidence on the ability of decentralization to enhance preference matching and technical efficiency in the provision of health and education in developing countries. Many influential surveys have found that the empirical evidence of decentralization's effects on service delivery is weak, incomplete, and often contradictory. Our own unweighted reading of the literature concurs. However, when we organize quantitative evidence first by substantive theme, and then—crucially—by empirical quality and the credibility of its identification strategy, clear patterns emerge. Higher-quality evidence indicates that decentralization increases technical efficiency across a variety of public services, from student test scores to infant mortality rates. Decentralization also improves preference matching in education, and can do so in health under certain conditions, although there is less evidence for both. We discuss individual studies in some detail. Weighting by quality is especially important when quantitative evidence informs policy-making. Firmer conclusions will require an increased focus on research design, and a deeper examination into the prerequisites and mechanisms of successful reforms.